ANALYSIS OF THE RESULTS OF EXPERIMENTAL RESEARCH OF THE DESIGN OF A GEARED-ROLLER MECHANISM WITH A FLEXIBLE ELEMENT (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2026)
This paper presents an analysis of the results of experimental studies on the design of a gear mechanism with a flexible element. The research includes the determination of the main operating parameters, investigation of structural features, as well as kinematic and dynamic analysis of the mechanism. Based on the obtained experimental results, scientific and technical solutions aimed at improving the performance and reliability of the gear mechanism are proposed. The research findings are of practical importance for the design and optimization of gear mechanisms.